Pedagogical framework on active learning in ordinary classroom - Hanipah , Hussin (2011)
Active learning methodology has become a preferred way to change the traditional teacher centered classroom into the newer student centered approach to learning. This paper describe the case study on some program on active learning in various faculty in Higher education in Malaysia. The statement of the problem in the program is how can an active learning methodology be implemented to assure that a student learns through the techniques established in active learning within a new pedagogical framework. This paper aim to present some ideas of how to use active learning techniques in the lectures in ordinary classroom in Malaysia (more than 30 students), and describe how training on active learning is successfully within twelve {12) programs during 201. the participants among engineering, information communication technology, management and entrepreneurship lecturers at Teknikal Universiti Malaysia Melaka, Cosmopoint International College, Polytechnic and Community College. They were more than 30-40 participants every training program. The main idea in the program is to use inductive, active learning, with many small exercises/ group discussions during the training session to show the example of how to apply some techniques in their own classroom. They were ten (10) actives learning frameworks/formats were introduced to the participants. More then 33 lesson plan in active learning develop and ready to use in ordinary classroom. The framework/format of active learning contains some visualize, design, and implement stage from the cooperative learning principle.